2015
DOI: 10.3354/ame01724
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the marine diatoms Pseudo-nitzschia multiseries and P. pungens to inhibit the growth of co-occurring phytoplankton via allelopathy

Abstract: Diatoms within the genus Pseudo-nitzschia can form near-monospecific blooms in both natural and iron-fertilized high-nutrient, low-chlorophyll (HNLC) regions and can have detrimental impacts on marine ecosystems. Here, we demonstrate the ability of P. pungens isolated from the South China Sea and 2 strains of P. multiseries isolated from the Bay of Fundy, Canada, to produce extracellular compounds capable of lysing and/or inhibiting the growth of multiple phytoplankton species. Since the allelopathic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Pseudo nitzschia multiseries can form blooms in coastal and ocean, which have harmful impact on marine ecosystems (Xu et al, 2015). Meanwhile, the neurotoxin was produced by this species can cause amnesic shellfish poisoning in both marine mammals and human beings (Dortch et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudo nitzschia multiseries can form blooms in coastal and ocean, which have harmful impact on marine ecosystems (Xu et al, 2015). Meanwhile, the neurotoxin was produced by this species can cause amnesic shellfish poisoning in both marine mammals and human beings (Dortch et al, 1997).…”
mentioning
confidence: 99%
“…In the past several years, numerous data for plastid genomic sequences in algae have been reported and being applied in the phylogeny genome (Maul et al, 2002;Oudot-Le Secq et al, 2007;Wand et al, 2013) due to the slow evolutionary rate and independent genetic mechanism of plastid (Bock & Knoop, 2012). Up to date, the research of P. multiseries mainly focus on the mechanism of blooming and toxic produce (Xu et al, 2015), there is still lack the plastid genome of P. multiseries. To gain further insight into its gene content, structure and evolutionary relationships, the whole plastid genome of P. multiseries was obtained.…”
mentioning
confidence: 99%
“…In a highly mixed and disturbed environment, enhanced competitive ability for resources is probably the main factor favouring the dominance of certain species. However it is interesting to note that field and laboratory experiments have shown that Skeletonema and Pseudo-nitzschia species can release allelophatic compounds (e.g., Lundholm et al, 2005;Yamasaki et al, 2010;Xu et al, 2015) that could also be a factor in promoting mono-specific blooms in the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Even though domoic acidan N-based toxin known to be excreted by Pseudonitzschia spp.-has been reported not to present allelopathic effects (Lundholm et al, 2005), there are indications of allelopathy due to other toxins excreted by Pseudo-nitzschia spp. (Xu et al, 2015).…”
Section: P-limitationmentioning
confidence: 95%